2022
DOI: 10.2196/28861
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Multiple Inputs Into an Artificial Pancreas System: Narrative Literature Review

Abstract: Background Type 1 diabetes (T1D) is a chronic autoimmune disease in which a deficiency in insulin production impairs the glucose homeostasis of the body. Continuous subcutaneous infusion of insulin is a commonly used treatment method. Artificial pancreas systems (APS) use continuous glucose level monitoring and continuous subcutaneous infusion of insulin in a closed-loop mode incorporating a controller (or control algorithm). However, the operation of APS is challenging because of complexities aris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Our study is in relation to short-term glucose prediction as we follow the fixed prediction horizon strategy, but with a focus on postprandial data only. Moreover, our study is in line with the second category of postprandial glucose prediction, but targeting the joint prediction of postprandial hyperglycemia and hypoglycemia, and relying on only the CGM sequence which circumvents extra burdens such as estimating meal carbohydrates [22], [23].…”
Section: B Postprandial Glucose Predictionmentioning
confidence: 67%
“…Our study is in relation to short-term glucose prediction as we follow the fixed prediction horizon strategy, but with a focus on postprandial data only. Moreover, our study is in line with the second category of postprandial glucose prediction, but targeting the joint prediction of postprandial hyperglycemia and hypoglycemia, and relying on only the CGM sequence which circumvents extra burdens such as estimating meal carbohydrates [22], [23].…”
Section: B Postprandial Glucose Predictionmentioning
confidence: 67%
“…The factitious “too rapid” assertion also deflects the many advances in continuous glucose monitoring (CGM) devices, insulin dosage-predicting algorithms, precision-dosing insulin pumps, open and closed loop systems, and the “artificial pancreas” (AP) [ 6 ]. To this point, a recent, comprehensive review of multiple input AP systems [ 57 ], identified two persistent challenges: lag times in acquiring blood glucose concentration data, and delays in absorption of insulin from SC depots. Our study is relevant to the latter concern, which echoes an earlier sentiment: for APs (and similar approaches) to achieve their full potential, the “applied insulin should induce ideally an instantaneous effect” [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The factitious "too rapid" assertion also deflects the many advances in continuous glucose monitoring (CGM) devices, insulin dosage-predicting algorithms, precision-dosing insulin pumps, open and closed loop systems, and the "artificial pancreas" (AP) [6]. To this point, a recent, comprehensive review of multiple input AP systems [54], identified two persistent challenges: lag times in acquiring blood glucose concentration data, and delays in absorption of insulin from SC depots. Our study is relevant to the latter concern, which echoes an earlier sentiment: for APs (and similar approaches) to achieve their full potential, the "applied insulin should induce ideally an instantaneous effect" [4].…”
Section: Discussionmentioning
confidence: 99%